Recycling and reuse of rusted iron particles containing core-shell Fe-FeOOH for ibuprofen removal: Adsorption and persulfate-based advanced oxidation. (20th March 2018) - Yin, Ran; Sun, Jianliang; Xiang, Yingying; Shang, Chii
Abstract: This paper describes the reuse of rusted iron particles recycled from used heat pads to remove ibuprofen through adsorption and persulfate-based advanced oxidation. The recycled rusted iron particles (RRIP) contained α-FeOOH and amorphous FeOOH on the shell and zero valet iron (Fe 0 ) in the core. The RRIP had an adsorption capacity of 3.47 mg/g towards ibuprofen, which was 4.8 times higher than that of the synthetic α-FeOOH. The stronger ibuprofen adsorption of RRIP was due to the larger specific surface area. The RRIP activated persulfate to generate both sulfate radicals (SO4 − ) and hydroxyl radicals (OH), which degraded the adsorbed and dissolved ibuprofen. Persulfate was activated primarily by surface bound Fe(II) that was in-situ formed from the interactions of the surface FeOOH with the Fe 0 cores. The adsorption enriched IBP on the FeOOH surface and accelerated the overall IBP degradation. RRIP had a saturation magnetization of 0.6 emu/g, which made it magnetically separable. The RRIP magnetically separated from the treated water were repeatedly reused with less than a 10% drop in adsorption capacity in each cycle. Ibuprofen was degraded by SO4 − and OH through hydroxylation, decarboxylation and sequential oxidation. The recycled waste iron particles are demonstrated to be promising adsorbents-and-catalysts for the removal of pharmaceuticals and personal care products from contaminated water by adsorption, and together with persulfate, by catalytic advanced oxidation. Graphical abstract: Image 1 Highlights: Rusted iron particles recycled from used heat pads contain core-shell Fe-FeOOH. RRIP exhibits strong ibuprofen adsorption. RRIP activates persulfate to generate SO4 − and OH and degrade ibuprofen. A pathway of ibuprofen degradation induced by SO4 − and OH is proposed. RRIP is magnetically separable and can be regenerated from the interaction with persulfate.